How soon does modern contraceptive use starts after sexual debut in Africa? Survival analysis of timing and associated factors among never-in-union women (2021)
While studies abound on the utilization of modern contraceptive (MC), the timing of its uptake after sexual debut has not been given fair attention in the literature. This study estimated the time to MC uptake after sexual debut and identified the factors associated with the timings among the ever-had sex never-in-union (EHS-NIU) women in Mozambique, Nigeria and Cote d’Ivoire and adopted the health belief model. This was a cross sectional study using the Mozambique, 2011, Nigeria, 2013 and Cote d’Ivoire, 2014 DHS data. The analysis was limited to 8,251 EHS-NIU women: Mozambique (1800), Nigeria (4082) and Cote d’Ivoire (2369). Descriptive statistics, survival analysis, log-rank tests, and multivariable Cox proportional hazard regression were used at p = 0.05. Over a third (38%) of the EHS-NIU women had ever used MC: Mozambique (26%), Nigeria (47%) and Cote d’Ivoire (32%). While the median time to first MC use was 2 years across the countries, the overall median survival time was 11 years: Nigeria (7 years), Cote d’Ivoire (17 years) and Mozambique (18 years). The hazard of MC was 92% (Hazard Ratio (HR)=1.92, 95% Confidence Interval (CI): 1.74–2.12) higher among EHS-NIU women in Nigerian compared to those in Cote d’Ivoire. Compared with the EHS-NIU women aged 15–19 years, the hazard of MC uptake was 71% lower in Nigeria (adjusted Hazard Ratio (aHR)=0.29, 95% CI: 0.52–0.65), 43% lower in Mozambique (aHR=0.57, 95% CI: 050–0.67) and 49% lower in Cote d’Ivoire (aHR=0.51, 95% CI: 040–0.65) among those aged 20–24 years. EHS-NIU women with higher education, who lives in urban areas, who delayed sexual debut, who frequently listened to the radio, in richest wealth quintiles had earlier uptake of MC. There were low lifetime prevalence and late uptake of MC among ever-had sex never-in-union women in Mozambique, Nigeria, and Cote d’Ivoire. The timing of MC uptake was associated with respondents’ age, age at sexual debut, place of residence, educational attainment, wealth quintile, number of children ever born, radio listening frequency and regions of residence.